Strategi Pemgembangan Sektor Potensial di Desa Legok Kaler, Kabupaten Sumedang - Riska Novitasari; Brian Rinaldy Irsyad; Arini Hardjanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The industrial sector in the Legok Kaler Village is classified as a small scale or household scale industry that has the potential to become a superior product of the village. Therefore, the majority of the livelihoods of the people of Legok Kaler Village are excavated workers, farmers, and entrepreneurs. Programs related to agriculture, skills and social development are formulated in Legok Kaler Village to help empower local communities so that they are expected to increase competitiveness, added value, and knowledge related to local resource management so that community welfare can be achieved. The results obtained from the activity are the implementation of Ecobrick which is one way of handling plastic waste by packaging clean and dry plastic so that it becomes a useful item. Activities can provide an introduction to ecobrick as the latest method of sustainable waste management and provide training and practice on making ecobrick. In addition to these activities there is an activity of analyzing the economic benefits of sand mining. The results of this analysis can be used as a suggestion for village officials to make policies in managing the management and utilization of sand in the Legok Kaler Village Keywords: ecobrick, Legok Kaler Village, sand excavation